Effects of inert organic and inorganic anions on the rates of intramolecular general base-catalyzed reactions of ionized phenyl salicylate (PS-) with piperidine in the presence of cationic micelles - Khan, M.N.; Yusoff, R. (Journal of Physical Organic Chemistry, 2001)
Pseudo-first-order rate constants (k(obs)) for piperidinolysis of PS- follow the relationship k(obs) - k(0)= k(n)(obs) Pip(T) (Pip(T) = total concentration of Pip) at a constant CTABr(T) (total concentration of cetyltrimethylammonium bromide), MX (inert salt concentration) and 35 degreesC. The values of k(n)(obs) at different CTABrT (ranging from 0.005 to 0.02 M) and MX follow the relationship k(n)(obs) = (k(w)(n) + k(w)(n) Psi MX + KnsM K-N K-S(0)CTABr(T))/( 1 + Psi MX + K-S(0) CTABr(T)), where k(w)(n) = k(n)(obs) at CTABr(T) = MX = 0, Psi is an empirical parameter and K-S(0) is the CTABr micellar binding constant of PS- in the absence of MX. The magnitude of Psi is attributed to the ability of X- to expel PS- from micellar pseudophase to the aqueous pseudophase. The values of Psi vary in the order Psi (sodium cinnamate) >Psi (sodium 4-methoxybenzoate) >Psi (sodium 2-chlorobenzoate) >Psi (disodium isophthalate) >Psi (disodium phthalate) >Psi (sodium sulfate) >Psi (disodium fumarate). The values of k(M)(ns) K-N (k(M)(ns) = k(M)(n)/V-M, where k(M)(n) is the second-order rate constant for the reaction of Pip with PS- in the micellar pseudophase and V-M is the micellar molar volume in M-1 and K-N represents CTABr micellar binding constant of Pip) are not significantly affected by the presence of MX into the reaction mixtures.